DREB Genes as Regulators of Drought Response in Maize: Molecular Mechanisms and Physiological Adaptation - Elisa; Nur Awaliah Duprah; Rachmawaty (Indonesian Journal of Biology Education, 2026)
Drought stress is one of the major limiting factors in maize (Zea mays) productivity, affecting the plant’s physiological, metabolic, and molecular processes. One of the important regulators in drought response is the Dehydration-Responsive Element Binding (DREB) gene, which belongs to the AP2/ERF transcription factor family. This article aims to comprehensively review the molecular mechanisms of DREB genes and their effects on the physiological adaptation of maize under drought stress conditions. The method used is a literature study of 35 selected scientific articles published between 2021 and 2026. The results of the review indicate that DREB functions as a central regulator that activates stress-responsive genes by binding to DRE/CRT elements in the promoter region of target genes, through both ABA-dependent and ABA-independent pathways. The activation of DREB contributes to osmotic adjustment, enhancement of the antioxidant system, stabilization of cell membranes, regulation of transpiration, and maintenance of photosynthesis. In addition, DREB genes have significant potential in biotechnology applications, including genetic engineering, utilization of endogenous genes, and as molecular markers in drought-tolerant maize breeding programs. Therefore, DREB represents a key component in the development of drought tolerance improvement strategies based on molecular approaches.